1 Kings 16 - 2 Kings 16 - McKenzie, Steve (W. Kohlhammer GmbH, 2018)
This volume makes use of diverse methods and approaches to offer fresh treatments of 1 Kings 16 - 2 Kings 16 both synchronically and diachronically. Among its major contributions are a detailed text-critical analysis that frequently adopts readings of the Old Greek and Old Latin and, at the same time, a reexamination of the variant chronologies for the kings of Israel and Judah that argues for the priority of the one in the Masoretic Text. The book presents a new theory of the compositional history of these chapters that ascribes them mostly to the hand of a postexilic "Prophetic Narrator" who reworked older legenda, especially about Elisha, and effectively shaped Kings into the work we have today. This volume makes use of diverse methods and approaches to offer fresh treatments of 1 Kings 16 - 2 Kings 16 both synchronically and diachronically. Among its major contributions are a detailed text-critical analysis that frequently adopts readings of the Old Greek and Old Latin and, at the same time, a reexamination of the variant chronologies for the kings of Israel and Judah that argues for the priority of the one in the Masoretic Text. The book presents a new theory of the compositional history of these chapters that ascribes them mostly to the hand of a postexilic "Prophetic Narrator" who reworked older legenda, especially about Elisha, and effectively shaped Kings into the work we have today
Keywords: Altes Testament; Elija-Erzählungen; Prophetenforschung